ROLE OF RESEARCH/ACADEMIC IN POLICY FORMULATION - Muluk, M. R. Khairul; Winoto, Suhartono (Jurnal Aplikasi Manajemen, 2018)
Research and development have a strategic role in formulating and implementing the policy. Research and development is one important step in order to produce a new idea. This article has a purpose produce a picture the existence of the difference between the point of view of academics with the point of view of a practitioner in formulating and implementing the policy.This article produced based on data collection started from focus group discussion and seminar. The results of analysis from focus group discussion, strengthened by seminar-seminar both at the local, national and international.The topic of the study subjects of many times successfully identified obstacles the role of academics and analysis the role of academics and the benefit of involvement academics.A new idea produced by academics cannot always directly applied by a practitioner. Any different and gap between the results of the study with the application of policy is caused by several factors. The differences that appear among others the different the time, different conception, different audience, different motivation and different consequences. There are 3 (three) way academics in influencing policy, through policy, the policy of research and development, and education policy and training (Adam, 2014). There are 3 (three) the key to strengthen the role of academics in the formulation policy among others network, reputation, and expectations.